Cryotherapy for Primary Treatment of Prostate Cancer: Intermediate Term Results of a Prospective Study from a Single Institution - S. Alvarez Rodríguez; F. Arias Fúnez; C. Bueno Bravo; R. Rodríguez-Patrón Rodríguez; E. Sanz Mayayo; V. Hevia Palacios; F. J. Burgos Revilla (Prostate Cancer)
Purpose. Published data about cryotherapy for prostate cancer (PC) treatment are based on case series with a lack of clinical trials and the inexistence of a validated definition of biochemical failure. A prospective study with standardized followup protocol was conducted in our institution. Material and Methods. Prospective study of a series of cases including 108 patients diagnosed with localized PC at clinical stage T1c-T2c treated by primary cryoablation and median followup of 61 months. Criteria of biochemical recurrence were unified according to the American Society for Therapeutic Radiology and Oncology (ASTRO). End points were biochemical progression-free survival (BPFS), cancer-specific survival, and overall survival. Rate of complications was reported. Results. The BPFS for low-, medium-, and high-risk patients was 96.4%, 91.2%, and 62.2%, respectively. Cancer-specific survival was 98.1%. Overall survival reached 94.4%. Complications included incontinence in 5.6%, urinary tract obstruction in 1.9%, urethral sloughing in 5.6%, haematuria in 1.9%, perineal pain in 11.1%, and prostatorectal fistula in 0.9%. Erectile disfunction was found in 98.1%. Conclusions. Cryotherapy is an effective and minimally invasive treatment for primary PC in well-selected cases, with low surgical risk and good results in terms of BPFS, cancer-specific survival, and overall survival.